2023
DOI: 10.1039/d2cp05119b
|View full text |Cite
|
Sign up to set email alerts
|

Conformational isomeric thermally activated delayed fluorescence (TADF) emitters: mechanism, applications, and perspectives

Abstract: Thermally activated delayed fluorescence (TADF) materials have received enormous attention and the mechanism behind has been continuously in-depth investigated. Currently, it is found that some donor-acceptor (D-A) type TADF emitters...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…We anticipate that the higher energy barrier resulted in a more stable flat conformer at the ground state, which, along with the excited state flattening of the twisted conformer (twisting → flat geometry), led to the significant enhancement of the AVP feature from the flat conformer of BPT3 compared with the other two derivatives. Since F1 is the most stable conformer for all molecules, the relative distribution of the conformers can be further estimated based on the Boltzmann distribution, as shown below 56,57 = ( ) ( )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipate that the higher energy barrier resulted in a more stable flat conformer at the ground state, which, along with the excited state flattening of the twisted conformer (twisting → flat geometry), led to the significant enhancement of the AVP feature from the flat conformer of BPT3 compared with the other two derivatives. Since F1 is the most stable conformer for all molecules, the relative distribution of the conformers can be further estimated based on the Boltzmann distribution, as shown below 56,57 = ( ) ( )…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that the higher energy barrier resulted in a more stable flat conformer at the ground state, which, along with the excited state flattening of the twisted conformer (twisting → flat geometry), led to the significant enhancement of the AVP feature from the flat conformer of BPT3 compared with the other two derivatives. Since F1 is the most stable conformer for all molecules, the relative distribution of the conformers can be further estimated based on the Boltzmann distribution, as shown below , where E , k B , j , and T represent conformational relative energy, Boltzmann constant, total number of conformers, and temperature, respectively. This relative distribution of conformers with varying temperatures agrees well with our experimental results (Figures e,f and S26), where decreasing temperatures lead to no significant change in the total emission intensity of both emission bands.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Organic luminescence molecules typically exhibit strong vibrational relaxation (with rates ranging from 10 12 to 10 15 s À1 ) and strong vibrational coupling between the excited state and ground state; as a result, their emission spectra are relatively broad, and developing narrowband TADF molecules is a longstanding challenge in the field of electroluminescence. [18][19][20][21][22][23][24] Researchers have made great efforts in this field. For the first time, Duan et al reported a series of efficient greenemitting multi-resonance induced thermally activated delayed fluorescence (MR-TADF) materials by amplifying the influence of the skeleton and peripheral units.…”
Section: Introductionmentioning
confidence: 99%
“…11–17 Organic luminescence molecules typically exhibit strong vibrational relaxation (with rates ranging from 10 12 to 10 15 s −1 ) and strong vibrational coupling between the excited state and ground state; as a result, their emission spectra are relatively broad, and developing narrowband TADF molecules is a longstanding challenge in the field of electroluminescence. 18–24…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27] In recent years, phenothiazine has attracted significant attention owing to its potential for a variety of optoelectronic applications such as organic light-emitting diodes (OLEDs), thermally activated delayed fluorescence (TADF) materials, stimuli responsive materials, and chemosensors. [28][29][30][31][32][33][34] In the solid state, the central thiazine ring of the phenothiazine moiety results in the conformational changes, and the S and N atoms potentially trigger supramolecular interactions, which can affect its photophysical properties. 35,36 Tetraphenylethylene (TPE) is a widely used AIEgen due to its non-planar twisted structure and is advantageous for optoelectronic applications such as organic light emitting diodes (OLEDs), mechanosensors, memory devices, data storage devices, and many more.…”
Section: Introductionmentioning
confidence: 99%